Bulk properties of the medium produced in relativistic heavy-ion collisions from the beam energy scan program - STAR Collaboration (Physical Review C, 2017)
We present measurements of bulk properties of the matter produced in Au+Au collisions at √sNN=7.7,11.5,19.6,27, and 39 GeV using identified hadrons (π±, K±, p, and ¯p) from the STAR experiment in the Beam Energy Scan (BES) Program at the Relativistic Heavy Ion Collider (RHIC). Midrapidity (|y|<0.1) results for multiplicity densities dN/dy, average transverse momenta ⟨pT⟩, and particle ratios are presented. The chemical and kinetic freeze-out dynamics at these energies are discussed and presented as a function of collision centrality and energy. These results constitute the systematic measurements of bulk properties of matter formed in heavy-ion collisions over a broad range of energy (or baryon chemical potential) at RHIC.
Keywords: dept.phy; peer-reviewed